Incorporating logic of indigeneity in safeguarding indigenous knowledge of medicinal plants in Malaysia: case study of the Bidayuh in the district of Serian, Sarawak / Jasmine Edmund Andrew - Andrew, Jasmine Edmund (2016)
In recent years there has been a remarkable revision of the negative perceptions on knowledge traditionally held and practiced by indigenous peoples. A particular aspect of traditional knowledge that has been attracting much attention is indigenous people's knowledge and uses of medicinal plants. This indigenous knowledge has attracted particular attention for the economic potential it brings from new drug development, as leads provided by indigenous use constitute an important costsavings factor in research and development. However, knowledge of medicinal plants among indigenous communities is facing the threat of erosion due to rippling forces of globalization and modernization. Studies among the country's indigenous communities have indicated that Malaysia is equally affected by this phenomenon. The impending loss of this valuable resource has stimulated policy intervention for affirmative action both at the international and national levels aimed at preserving, reinforcing, recording or adapting indigenous knowledge on medicinal plants, primarily through documentation and recording of medicinal plants specie and their uses in traditional treatments. Malaysia's recent membership to the 2003 Convention on Safeguarding Intangible Cultural Heritage provide an opportunity for an indigenous stakeholder lens at policy intervention towards ensuring viability of the knowledge. The findings indicated that in spite of a lack of awareness of policy on traditional knowledge of indigenous plants, there is high appreciation and value of the knowledge among the elder generation as a cultural heritage and as a first course of treatment for illnesses and ailments; and that awareness and education on the value of this traditional knowledge among the younger generation impacts upon intergenerational transmission of knowledge. The study also identified several constraints and factors affecting public education and awareness of government policies and programs, as well as inter-generational transmission of knowledge and management of this knowledge among rural populations. Suggestions by the younger generation on ways to facilitate inter-generational transmission were incorporated into a logic model to encourage viability of the knowledge among indigenous communities in Malaysia.